Da escola ao mangue : a utilização do jogo como ferramenta pedagógica para o ensino das ciências ambientais - Azevedo, Mariana Morais (2018)
With the increase in population, cities grow disorderly and occupy areas that were previously natural, consequently, the lack of basic sanitation and housing increases, leading to environmental degradation. In this context is the region of Taiçoca de Fora, located in Nossa Senhora do Socorro county, where the population suffers with the problems created by the disorderly growth of the villages there, lack of adequate basic sanitation, degradation of the mangrove area, river, and also where the economic activities of the community are developed and are linked to the ecosystem, including fishing. The school as one of the places of possible knowledge integration, based on interdisciplinarity, can contribute to the reflection about these socio-environmental relations through the Environmental Sciences teaching. The present study aims to analyze a proposal of pedagogical practice in the formal and community school environment for the Environmental Sciences teaching in the final years of Elementary School. To this end, bibliographical studies will be carried out regarding the field lessons, conservation and Environmental Education and interdisciplinarity. From the methodological point of view, through induction, the first step will be the application of a questionnaire for the students of the 6th and 8th grades, corresponding to the amount of 49 students from the morning period of João Arlindo de Jesus State School, located in the Taiçoca de Fora district, in order to investigate the students conceptions regarding the environmental theme of ecosystem and environmental degradation of mangrove, about the water resources and the soil use and occupation. Next, the execution of the activities proposed and elaborated in agreement with the teachers of the disciplines of Arts, Sciences, Geography, Portuguese Language and Writing, whose main theme is the mangrove ecosystem, water resources and environmental impacts and the realization of actions in the perspective of formal and non-formal environmental education in the same village, constituting the pedagogical practice in the form of a game and the implementation of actions in the perspective of formal and non-formal environmental education of learning, which will be developed by the students. In addition to the production of the game "Knowledge Trail: Manguetown2" as a pedagogical tool for the Environmental Sciences teaching. It is hoped to contribute to raising awareness about environmental issues through educational actions related to mangroves, water resources and the environmental impacts of the community in which the student is inserted. In addition, to make possible through the ludic the dialogue of concepts in the curricular subjects and encourage the contact of the school community with the environment.